Public awareness of low vision rehabilitation in China - Li, Xiaoman; Zhu, Ruyi; Liu, Yuanyuan; Zhang, Jianing; Hu, Xiaoyue; Chi, Qi; Lin, Na; Chen, Jie (Frontiers in Medicine, 2025)
ObjectiveTo demonstrate public awareness of low vision rehabilitation (LVR) in China and identify related influencing factors.MethodsThis cross-sectional study assessed low vision rehabilitation awareness using a Delphi method validated questionnaire. The questionnaires were distributed through Vision China conferences (2022–2023) and representative hospitals in all provinces across China, targeting public and vision professionals.Results1,482 questionnaires (360 were from visually impaired individuals) were collected, including 952 from the public and 530 from vision professionals. The mean total scores accounted for 37.0% and 55.6% of the maximum scores, respectively. For the public, individuals with higher education, good visual acuity, working in medical system, and having eye check yearly or more frequent were associated with better awareness of LVR. For vision professionals, participants aged over 40 years old, with better visual acuity, and knowing the low vision referral process demonstrated a better awareness of LVR. The main sources of LVR information for the public were doctors' advice (about 29%) and news media/online information (about 28%).DiscussionThe awareness of LVR in China is insufficient in both the public and vision professionals. Regular eye checks, doctors' advice, and scientific education are essential to improve the awareness of the public. It is crucial to develop low-vision education in the medical curriculum and expand low-vision continuing education and forums to improve awareness among vision professionals.